Suplementasi Asam Folat pada Wanita Hamil Trimester Pertama untuk Pencegahan Preeklampsia: Studi Kohort Retrospektif - Kamri, Andi Maulana; Putra , Bayu; Kosman, Rachmat; Basri, Putri Septiani (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Preeclampsia is a disorder characterized by hypertension and proteinuria that manifests during gestation. Various vitamins can influence food consumption during pregnancy. Folic acid supplementation is known to reduce preeclampsia risk, yet adherence remains low among pregnant women. The objective of the research is to identify risk variables and dosage efficacy associated with folic acid utilization. This study employs an retrospective cohort study and utilizes retrospective data collection. Data was gathered from Cahaya Ibu Pharmacy Store in Makassar, encompassing a total of 164 patients. A chi-square statistical study indicated a substantial risk association between pregnant women and the onset of hypertension in comparison to nonpregnant individuals, with a p-value of 0.001. Pregnant women had twice the risk, as shown by an odds ratio of 1.9. The study of Fisher's test data indicates a correlation between patient age and hypertension condition. The findings indicate no substantial correlation between the two variables, with a p-value of 0.523. The findings indicate a substantial correlation between the mitigation of raised blood pressure risk and the consumption of folic acid. The early use of folic acid during pregnancy planning significantly diminishes the likelihood of preeclampsia. Risk factors for preeclampsia include insufficient folic acid consumption, the duration of folic acid supplementation, and the pregnancy status of individuals with a disease risk of up to 98%. Less at age 30 years old, the consumption of folic acid may reduce the risk.